2017
DOI: 10.1038/cddis.2017.142
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a induces loss of 5-hydroxymethylcytosine and promotes metastasis of hepatocellular carcinoma through a TET–SOCS1–MMP9 signaling axis

Abstract: Ten eleven translocation (TET) enzymes convert 5-methylcytosine (5-mC) to 5-hydroxy-methylcytosine (5-hmC) and have crucial roles in biological and pathological processes by mediating DNA demethylation, however, the functional role of this epigenetic mark and the related enzymes in hepatocellular carcinoma (HCC) progression remains unknown. Here, we demonstrated that TET-family enzymes downregulation was one likely mechanism underlying 5-hmC loss in HCC. We found that miR-29a overexpression increased DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 44 publications
5
58
0
Order By: Relevance
“…MMP‐2/9 plays an important role in cancer metastasis, and IL‐17A is widely accepted as a regulator for MMP‐2 and MMP‐9 . As expected, our result showed that IL‐17A up‐regulated the expressions of MMP‐9 and MMP‐2 in a time‐dependent pattern compared to the control group in U251 and U87 cells.…”
Section: Resultssupporting
confidence: 84%
“…MMP‐2/9 plays an important role in cancer metastasis, and IL‐17A is widely accepted as a regulator for MMP‐2 and MMP‐9 . As expected, our result showed that IL‐17A up‐regulated the expressions of MMP‐9 and MMP‐2 in a time‐dependent pattern compared to the control group in U251 and U87 cells.…”
Section: Resultssupporting
confidence: 84%
“…miR-29a ( Figure 2A) promoted metastasis by silencing suppressor of cytokine signaling 1 (SOCS1), an inhibitor of metastatic signal transduction (52,53), due to methylation of its DNA, and subsequent activation of Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) signaling (52). miR-29a directly targets ten eleven translocation enzymes (TET) which convert 5-methylcytosine to 5-hydroxy- methylcytosine, resulting in inhibition of SOCS1 promoter demethylation (52)(53)(54). miR-29a promotes proliferation and invasion of HCC cell lines SMMC-7721 and HCCLM3 and increases tumor growth and lung metastasis of orthotopically implanted HCCLM3 and SMMC-7721 HCC cells transfected with miR-29a (52).…”
Section: Up-regulated Mirs Mediating Metastasismentioning
confidence: 99%
“…miR-29a directly targets ten eleven translocation enzymes (TET) which convert 5-methylcytosine to 5-hydroxy- methylcytosine, resulting in inhibition of SOCS1 promoter demethylation (52)(53)(54). miR-29a promotes proliferation and invasion of HCC cell lines SMMC-7721 and HCCLM3 and increases tumor growth and lung metastasis of orthotopically implanted HCCLM3 and SMMC-7721 HCC cells transfected with miR-29a (52). miR-29a overexpression is correlated with poor clinical outcome in patients with HCC and inhibition of TET-SOCS mediated signaling in HCC tissues.…”
Section: Up-regulated Mirs Mediating Metastasismentioning
confidence: 99%
“…In breast cancer, expression of miRNAs has been associated with clinical and molecular subtypes [10][11][12], progression [13][14][15], prognosis [16,17] and expression of oncogenes [18]. Importantly, miRNAs have been shown to regulate the expression of epigenetic regulators such as DNMTs and TETs [19,20]. We have previously shown how concerted alterations in copy number or promoter methylation affect miRNA expression in cis, resulting in up-regulation of oncogenic miRNAs and down-regulation of tumor-suppressor miRNAs [21].…”
Section: Introductionmentioning
confidence: 99%